1991
DOI: 10.2307/2445276
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast-DNA Variation in Tellima grandiflora (Saxifragaceae)

Abstract: Tellima grandiflora, a herbaceous, diploid (2n = 14) perennial, is distributed from the peninsula and panhandle of Alaska to central California. Restriction site variation of chloroplast DNA was surveyed in 51 populations representing the geographic range of T. grandiflora using 20 endonucleases. Two well‐differentiated clades of populations differing by 19 restriction site mutations and several length mutations are geographically structured. A northern group comprises populations from Alaska to central Oregon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

1993
1993
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 22 publications
0
21
0
1
Order By: Relevance
“…This is similar to other plants where the majority of the mutations occur in the single‐copy regions, mainly the large single‐copy region, rather than the inverted repeat which is more conserved (Palmer et al . 1985; Sytsma & Gottlieb 1986; Soltis et al . 1991; Byrne & Moran 1994; Butcher et al .…”
Section: Resultsmentioning
confidence: 99%
“…This is similar to other plants where the majority of the mutations occur in the single‐copy regions, mainly the large single‐copy region, rather than the inverted repeat which is more conserved (Palmer et al . 1985; Sytsma & Gottlieb 1986; Soltis et al . 1991; Byrne & Moran 1994; Butcher et al .…”
Section: Resultsmentioning
confidence: 99%
“…Introgression of chloroplast lineages where hybridization was not suspected has been observed in a number of species, e.g. Tellima grandiflora (Soltis et al ., 1991), Populus nigra (Smith & Sytsma, 1990), Salix melanopsis (see Reiseberg & Brunsfeld, 1992). Introgression from another species is unlikely in A. acuminata as the two lineages coalesce to a common ancestor.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have identified one or both of these regions as potential refugial sites in both animals and plants (e.g. Bernatchez & Dodson 1991; Soltis et al 1991; Hayes & Harrison 1992; O’Reilly et al 1993; Orti et al 1994; Talbot & Shields 1996). Southern California provides another potential refugial site, although more extensive sampling is needed to support this.…”
Section: Discussionmentioning
confidence: 99%